(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
This article examines the modes of objectification of a collective subject described as "Indian American", through the panoptic technologies of literature and cinema as utilised in the United States (US) in the aftermath of 9/11. Following the 2003 publication of the novel by Jhumpa Lahiri, The Namesake, Fox Searchlight Pictures released Mira Nair's cinematic adaptation in 2007. Published in the aftermath of the 9/11 event in the US, the story spans over three decades, telling of the diasporic experiences of a middle-class family of a minority culture, the Gangulis, from their immigration in the 1960s—which historically coincided with the rise of two contrasting social phenomena, Neoliberalism and the Oriental Other—to their present assimilated status into the mainstream American culture. We argue that the literary and cinematographic narratives of The Namesake are employed by the hegemonic state power to offer an antidote to the chronic insecurities unleashed by notions of both Neoliberalism and the Oriental Other. The study outlines the panoptic dimensions of both narratives and unpacks the way their visual, narrative and "characterological architectonics" correspond with what Michel Foucault calls "the carceral mechanisms of power". Novel and film thus act together to instantiate in the public the ideological interests of the capital which, in turn, mobilises the apparatus itself, doing so through narrative techniques that conscript the public into a unified scopic regime. In the diasporic world of The Namesake, as the article concludes, the individual difference is associated with social deviance, in a way that in society, the local subject and its individuality become a signifier of guilt, whereas, assimilation into global cultural pluralism is made synonymous with conformity and normativity.